2016
DOI: 10.36076/ppj/2016.19.e1135
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroscopic Sacroiliac Joint Injection: Is Oblique Angulation Really Necessary?

Abstract: Background: The conventional technique for sacroiliac (SI) joint injection involves aligning the anterior and posterior aspects of the SI joint under fluoroscopic guidance and then entering the SI joint in the most caudal aspect. Objective: We wish to highlight that there is no added advantage to aligning both the anterior and posterior joint lines of the SI joint as it is time consuming, associated with additional radiation exposure, and may make the entry into the posterior SI joint technically more difficul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“… 28 Both Khuba et al and Chauhan found that the oblique angulation may be unnecessary and that one might enter the lower part of the posterior joint in an anterior-posterior image alone allowing for access to the joint with lower fluoroscopy times. 29 , 30 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“… 28 Both Khuba et al and Chauhan found that the oblique angulation may be unnecessary and that one might enter the lower part of the posterior joint in an anterior-posterior image alone allowing for access to the joint with lower fluoroscopy times. 29 , 30 …”
Section: Methodsmentioning
confidence: 99%
“… 39 On the right side, at the S1 and S2 levels, the needles are placed at the 2:30, 4:00, and 5:30 positions. 29 At the same levels on the left, needles are placed at 9:30, 8:00, and 6:30 positions. 30 At the S3 level, needles are placed at 2:30 and 4:00 on the right and 9:30 and 8:00 on the left.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, fluoroscopy was used in a true-anteroposterior (AP) view. In the case series, sixty (60) sacroiliac joints were injected, with only four (4) joints showing incorrect contrast spread [ 17 ]. The authors concluded that aligning the anterior and posterior aspects of SI joint for fluoroscopic-guided SI joint injection was not necessary.…”
Section: Introductionmentioning
confidence: 99%